ANALYSIS OF THE EFFECT OF FUNDING DECISSIONS, MACROECONOMIC, AND PROFITABILITY ON THE VALUE OF FOOD AND BEVERAGES COMPANIES IN THE INDONESIA STOCK EXCHANGE PERIOD 2015-2018 - Astawinetu, Erwin Dyah; Handini, Sri; Istiono, Istiono (Universitas Dr. Soetomo, 2020)
This study aims to analyze the influence of funding, macroeconomic, and profitability decisions on the value of Food and Beverages companies in the Indonesia Stock Exchange in the period 2015-2018. The data used is the 2015-2018 annual financial statement data. The population is all food and beverage companies listed on the Indonesia Stock Exchange, and the study sample is 12 companies using purposive sampling.From the results of the study found that simultaneously there is a significant influence between funding decisions (DER and DAR), Macroeconomics (SBI) and Profitability (ROA and ROE) on firm value (PER) Based on hypothesis analysis it can be concluded that DAR, DER, and ROA partially have a significant effect on firm value. Whereas ROE and SBI do not have a significant effect on Company Value (PER). The contribution of the independent variable to the dependent variable is 46.9%, which means that the variable of the independent variable is able to explain the variability of the dependent variable by 46.9%, while 53.1% is explained by other variables outside the model studied.